Computer simulation methods in theoretical physics - Heermann, Dieter W. (Springer Berlin Heidelberg, 1990)
1. Introductory Examples -- 1.1 Percolation -- 1.2 A One-Particle Problem -- Problems -- 2. Computer-Simulation Methods -- Problems -- 3. Deterministic Methods -- 3.1 Molecular Dynamics -- Problems -- 4. Stochastic Methods -- 4.1 Preliminaries -- 4.2 Brownian Dynamics -- 4.3 Monte-Carlo Method -- Problems -- A 1. Random Number Generators -- A2. Program Listings -- References.
Keywords: Monte-Carlo-Simulation; Brownsche Dynamik; Molekulardynamik